2015
DOI: 10.1111/jai.12748
|View full text |Cite
|
Sign up to set email alerts
|

Diel cycle size-dependent trophic structure of neotropical fishes: a three year case analysis from 35 floodplain lakes in Colombia

Abstract: Investigated were whether fish assemblages in 35 neotropical floodplain lakes along the Magdalena River, Colombia (ranging from 4 to 2333 ha) have a trophic structure that is dependent on fish body size within the diel cycle (24 h), and whether any changes to the trophic structure of fish assemblages occur during the diel cycle. Sampling was done during diel cycles in the rainy seasons between 2008 and 2011 (ten lakes in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
1
1
Order By: Relevance
“…The high specialization of H. magdalenae to feed on decapods and terrestrial insects in Porce II suggests that in this reservoir there is a high availability of these prey organism or that H. magdalena individuals are successful predators, outcompeting other fish in consuming these food items. The feeding behavior of H. magdalenae in the studied reservoirs differs from that reported in natural environments like the floodplains of the Magdalena River, where this fish species acts as a generalist, consuming a wide variety of terrestrial and aquatic insects and incorporating vegetal material, such as leaves and seeds, into its diet [49].…”
Section: Discussioncontrasting
confidence: 61%
“…The high specialization of H. magdalenae to feed on decapods and terrestrial insects in Porce II suggests that in this reservoir there is a high availability of these prey organism or that H. magdalena individuals are successful predators, outcompeting other fish in consuming these food items. The feeding behavior of H. magdalenae in the studied reservoirs differs from that reported in natural environments like the floodplains of the Magdalena River, where this fish species acts as a generalist, consuming a wide variety of terrestrial and aquatic insects and incorporating vegetal material, such as leaves and seeds, into its diet [49].…”
Section: Discussioncontrasting
confidence: 61%
“…Although the omnivorous group is by far the most diverse, taxa composition is strongly dependent on the species assemblage in the different aquatic systems (Table ). In floodplain lakes Hernández‐Serna et al () also found that there is a foraging segregation during the diel cycle by body size and trophic group: small fishes forage during the day while larger fishes do so at night, and carnivores and detritivores forage during the night and omnivores by day.…”
Section: Current Status Of the Fish Knowledge In The Caribbean North‐mentioning
confidence: 95%